OPTIMALISASI GERAKA LITERASI SEKOLAH DENGAN POJOK BACA TERHADAP MINAT BACA PESERTA DIDIK KELAS VA SD NEGERI RAWU - Yuni Maulani Rahmah; Ujang Jamaludin; Reksa Adya Pribadi (STKIP Subang, 2023)
School literacy activities are one of the movement programs that the government implements to foster students' interest in reading. However, in reality students' interest in reading is still relatively low. The purpose of this study was to provide an overview of optimizing school literacy activities in the form of reading corners in increasing students' interest in reading. The research method used was descriptive qualitative research with the research subject being elementary school students, especially the VA class of SD Negeri Rawu. Data collection techniques used observation, interviews and documentation at SD Negeri Raawu. Data analysis used descriptive data analysis. The results of the study show the influence of the school literacy movement in the form of a reading corner on reading interest. The existence of a reading corner has a positive influence on reading interest in the VA class of SD Negeri Rawu. The emergence of interest and enthusiasm of students in reading and increased visits to read in the library. Keywords: reading corner; literacy; reading interest